Analysis of threats to research validity introduced by audio recording clinic visits: Selection bias, Hawthorne effect, both, or neither?. Issue 7 (July 2015) - Henry, Stephen G.; Jerant, Anthony; Iosif, Ana-Maria; Feldman, Mitchell D.; Cipri, Camille; Kravitz, Richard L.
Highlights We investigated factors associated with consent to audio record clinic visits. We examined the effect of recording on patient–clinician interactions. Few patient or clinician factors were associated with likelihood of consent. We found no significant effects of recording on patient–clinician interactions.